PAYMENT TRANSACTION PROCESSING SYSTEM DESIGN ON PT. AIR COMM - Dede Sopanudin; Irwan Bastian, SKom, MM (Jurnal Sistem Informasi, 1998)
With the design of information systems at the administrative and financial administration. Air Comm, can help the management in managing the payment transaction data in a faster and more accurate calculation of the payment transaction can be trusted so that the truth, and maintenance of the files can be more easily and security of the files can be maintained adequately, while also able to improve staff knowledge within the field of information technology.